(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
Strict environmental laws limit the emission of wastewaters formed in the manufacturing of plastics. We have developed a new method for the treatment of alkaline wastewaters, which we have given the name Boundary Layer Separation Method (BLSM). We have utilized the phenomenon that on the surface of an electrically charged electrode, ions can be enriched in the boundary layer, as compared to the liquid phase. The essence of the method is that – with an appropriately chosen velocity – the boundary layer can be removed from the wastewater, and the boundary layer, which is rich in ions, can be recycled. Electrosorption is a surface phenomenon, thus the formation of the boundary layer requires appropriate electrodes. Nickel pastille electrodes prepared with powder metallurgical methods and nickelized nickel electrodes prepared with electrolysis were used for the experiments. The phenomena on the electorde/solution interface were examined in flowing systems. The discharge of the diffuse part of the boundary layer was examined as the function of the flow rate. It is concluded that it is pointless to exceed the relative velocity of 25 cm/s in the case of nickel pastille electrodes and 10 cm/s in the case of nickelized nickel electrodes. Lastly, the ion transport with BLSM and the experimental device is presented. Electrochemical methods, such as BLSM have the advantage of not utilizing dangerous chemicals, only inert electrodes. An additional advantage is that they do not generate further pollutants.